Piety and plague - Mormando, Franco,Worcester, Thomas (Truman State Univ. Press, 2007)
The literature of plague and the anxieties of piety in sixth-century Byzantium / Anthony Kaldellis – Mice, arrows, and tumors : medieval plague iconography north of the Alps / Pamela Berger – Visualizing death : medieval plagues and the macabre / Elina Gertsman – The making of a plague saint : Saint Sebastian's imagery and cult before the Counter-Reformation / Sheila Barker – Protestants and plague : the case of the 1562-63 pest in Nuremberg / Ronald K. Rittgers – The Canker Friar : piety and intrigue in an era of new diseases / William Eamon – Poussin's Plague at Ashdod (Rome, 1630-31) : a work of art in multiple contexts / Elisabeth Hipp – Plague as spiritual medicine and medicine as spiritual metaphor : three treatises by Etienne Binet, S.J. (1569-1639) / Thomas Worcester – Pestilence, apostasy, and heresy in seventeenth-century Rome : deciphering Michael Sweerts' Plague in an ancient city / Franco Mormando
9781931112734
Keywords: Konferenzschrift; Plague; Piety; History; Medieval; Religion and Medicine; Socioeconomic Factors